Human disturbance impacts on rainforest mammals are most notable in the canopy, especially for larger‐bodied species. Issue 7 (7th May 2019) - Whitworth, Andrew; Beirne, Christopher; Pillco Huarcaya, Ruthmery; Whittaker, Lawrence; Serrano Rojas, Shirley Jennifer; Tobler, Mathias W.; MacLeod, Ross
Abstract: Aim: Community‐level assessments of how biodiversity responds to disturbance within forest habitats are often biased towards terrestrial‐based surveys. However, recent research suggests that arboreal communities of several indicator groups (ants, amphibians, beetles and butterflies) are more susceptible to human disturbance than their terrestrial counterparts, but what about wildlife at higher trophic levels? We assess responses to disturbance, from forest floor to canopy, of a key conservation flagship group: medium to large rainforest mammals. Location: The Manu Biosphere Reserve, southeast Peru. Methods: We deploy both arboreal and terrestrial camera traps to directly compare the response of arboreal and terrestrial mammal communities to rainforest degradation and disturbance. Results: We show that the arboreal mammal community is more susceptible to habitat disturbance than the terrestrial community. Furthermore, the largest‐bodied arboreal species, which are major seed dispersers, showed the greatest negative response to forest disturbance. The strongest predictors of occupancy probability for arboreal communities were focal tree connectivity and canopy cover, whereas surrounding forest loss and canopy height were there strongest predictors of terrestrial community occupancy, although these also had effects similar in size and magnitude on the arboreal community. Main conclusions: Conservation conclusions drawn from camera‐based studies focused on the terrestrial realm likely underestimate the impact of rainforest degradation to arboreal communities and on arboreal rainforest biodiversity in general. We highlight the importance of implementing arboreal research methods, capable of investigating conservation implications of anthropogenic disturbance across all vertical strata, for accurate conservation assessments and improving rainforest management and restoration strategies.